The Effectiveness of Laughter Therapy on Reducing Depression Levels in the Elderly: Literature Review - Primasari Mahardhika Rahmawati; Suhari; Akhmad Fajrul Rizqi (KHD Production, 2023)
Depression is a natural feeling disorder caused by cognitive dysfunction characterized by decreased mood and sadness. Laughter therapy is a way to help someone deal with problems such as stress, anger, and boredom. This study aimed to determine the summary of laughter therapy in the elderly. The method used is a literature review in the form of a literature review obtained from the PubMed, Google Scholar, and Garuda Ristekbrin databases. After going through the selection stage using the Joanna Briggs Institute (JBI) critical appraisal, 10 journals were obtained, 9 of which used quasi-experimental studies, and 1 of them used systematic reviews. , stress hormones will decrease and increase feelings of happiness Based on statistical tests showing that the results of all tests were positive, it can be concluded that there is an effect of giving laughter therapy on reducing the level of depression in the elderly after several interventions.